161k views
1 vote
Drag a statement or reason to each box to complete this proof.

If −6(x−4)=42, then x=−3

Statement Reason

1. Given

2.

3. x−4= −7 Simplifying

4. x−4+4= −7+4

5. x= −3 Simplifying

ANSWER CHOCIES

Simplifying, Addition Property of Equality, Division Property of Equality,
-6(x-4) = 42
------- -----
-6 -6 the = sign is suppose to be in the middle and the other -6 under 42. Also this is a choice to −6(x−4)=42

1 Answer

1 vote

Statements Reason

1.
-6(x-4)= 42 Given

2.
(-6(x-4))/(-6) = (42)/(-6) Division property of equality

" Division property of equality states that if we divide both sides of an equation by the same nonzero number, the equation remains equal".

3.
x-4 = -7 Simplifying

4.
x-4+4 = -7+4 Addition property of equality

"Addition property of equality states that if the same number is added to both sides of an equation, then the equality is still true".

5.
x = -3 Simplifying

Therefore, the solution to the equation
-6(x-4)= 42 is x = -3.

User Jennifer Therese
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.